Evaluation of Outcome of Type 2 Clavicular Fractures with Pre-Contoured Locking Compression Plates - Karki, Prateek; Shrestha, Dinesh; KC, Dipendra; Shrestha, Sabin; Ranabhat, Roshani; Yogi, Suchil; Giri, Sagar (Journal of Nepalgunj Medical College, 2019)
Background: Clavicular fracture is a common traumatic condition encountered around shoulder region in adult population, while mid-shaft fractures (Robinson’s type 2) are found to be a most common variety. Management trends have changed in recent years from conservative to surgery, considering the higher rates of malunion, nonunion and poorer functional outcomes when managed non-operatively. An open reduction and internal fixation with precontoured locking compression plates has been a backbone of treatment of these fractures for several years with the aim of anatomical reduction, stable fixation and early rehabilitation of affected shoulder. Objective: To evaluate the outcome of Robinson type 2 clavicular fractures managed surgically with precontoured locking compression plates. Methods: Prospective study of 100 adult patients with Robinson type 2 clavicular fractures managed surgically with precontoured locking compression plates from January 2017 to November 2019 at the department of orthopaedics of Nepalgunj Medical College, Kohalpur. Outcomes were evaluated radiologically as well as functionally on the basis of Constant and Murley’s scoring system. Result: Union was achieved in 98% patients with an average duration of 4.16 months with standard deviation of 1.23. Functional results were excellent in 80% and good in 17%. There were two major complications, one requiring reoperation and hardware removal due to deep infection while other went into nonunion. One patient sustained re-fracture within 2 weeks following implant removal after another trauma. Conclusion: Outcome of surgery was satisfactory with desirable result in almost all of the patients. The surgery was simple, easy to perform and was free from radiation exposure.